2021
DOI: 10.1155/2021/5590973
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Impairment Aggravates Cisplatin-Induced Ototoxicity

Abstract: Cisplatin is an efficacious anticancer agent, but its use is limited by ototoxicity and resultant irreversible sensorineural hearing loss. Cisplatin ototoxicity is associated with cochlear cell oxidative stress and mitochondrial damage. However, mitophagy is vital for maintaining mitochondrial quality and cellular metabolism. Accordingly, we investigated the role of mitophagy in regulating cisplatin-induced ototoxicity using the auditory cell line HEI-OC1. In this study, HEI-OC1 cells were treated with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Studies have revealed a tight relationship between mitophagy and SNHL, as well as the signi cance of mitophagy in preserving inner ear homeostasis (Zhang et al 2023). According to several studies, impairment of mitophagy can worsen hearing loss brought on by medications and other variables (Cho et al 2021;Kim et al 2021;Li et al 2023a), and up-regulation of mitophagy can reduce drug-induced ototoxic damage (Han et al 2023). The process of mitochondrial ssion is critical for mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed a tight relationship between mitophagy and SNHL, as well as the signi cance of mitophagy in preserving inner ear homeostasis (Zhang et al 2023). According to several studies, impairment of mitophagy can worsen hearing loss brought on by medications and other variables (Cho et al 2021;Kim et al 2021;Li et al 2023a), and up-regulation of mitophagy can reduce drug-induced ototoxic damage (Han et al 2023). The process of mitochondrial ssion is critical for mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Although low CUR and CUR-NP concentrations could protect OHCs from CDDP damage, the exact mechanism responsible for this protection remains unclear. CDDP is known to promote endogenous mitochondrial damage and HC apoptosis via upregulation of oxidative stress, which eventually leads to ototoxicity. , Additional reports revealed that enhanced ROS synthesis was a primary mechanism that regulates ototoxic drug-driven HC apoptosis. Excess ROS inhibits HC activity, impairs antioxidant defense, and promotes the mitochondrial release of the apoptotic factor cytochrome C. Mitochondrial apoptosis involves regulation by both pro- and antiapoptotic members of the Bax family of proteins, and Caspase-3 is the ultimate target of this process .…”
Section: Discussionmentioning
confidence: 99%
“…Currently,cisplatin induced ototoxicity is a major obstacles that limited the maximum e cacy for tumor patients.Previously studies demonstrated that miRNA was closely associated with hearing loss and considered as promising therapeutic targets [29] .A currently study reported mitophagy protected HEI-OC1 cells against cisplatin-induced ototoxicity [30] ,but the precise molecular mechanism remained to be further studied.In the present study,we investigated whether miR-34a/DRP1-meditaed mitophagy contributed to cisplatin-induced ototoxicity and sought to determined the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…HEI-OC1 cells were treated with various concentration cisplatin (10,20,30, and 40 uM) and detected the cell viability at 8,16,24, and 48 h after exposure.CCK-8 assay indicated that cisplatin exposure induced cytotoxicity of HEI-OC1 Cells in a dose-time dependent manner (Fig. 3A ).The cell viability was appropriately 45.2% in HEI-OC1 cell treated with 20 uM cisplatin for 24 h.Therefore,we chose 20 um cisplatin for 24h as the exposure concentration and time of the subsequent experiments.…”
Section: Cisplatin Induced Cytotoxicity Via Mitochondrial Dysfunction...mentioning
confidence: 99%